PENGARUH MOTIVASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT.TELKOM Tbk CABANG MAKASSAR - NURNANINGSIH NURNANINGSIH (Jurnal Mirai Management, 2020)
The results showed that: 1) External Motivation in PT. Telkom companies had a significant influence on performance productivity based on employee perceptions, 2) From the results of the analysis, the results showed that external motivation (Working Conditions, Good Bosses, Financial and Social Guarantees) had an effect towards the productivity of the company. While the analysis obtained from internal motivation (Exciting Work, Challenging Work, and Attractive Work) has an influence on productivity. Thus, the proposed hypothesis is proven, 3) External and internal motivation has a simultaneous effect on employee performance. This is evidenced by the coefficient of determination test, which is equal to 47% of employee performance is influenced by variations in the two variables used in the study, the remaining 53% is influenced by other factors, 4) External motivation is more dominantly influencing employee performance this is evidenced by external motivation regression coefficient greater than internal motivation, 5) Internal motivation is the most dominant influence on productivity is good communication between employees and supervisors of internal motivation is the work performance that is owned based on the research conducted. Keywords : “Motivation, Good Bosses , Financial and Social Guarantees”.